FEMALE STUDENTS' ABILITY BASED ON THEIR EDUCATIONAL BACKGROUND IN LEARNING ARABIC AT SHEIKH ALI HASAN AHMAD ADDARY STATE ISLAMIC UNIVERSITY, PADANGSIDIMPUAN - Ali Asrun Lubis (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2025)
The female students participating in this study come from various educational backgrounds, including general senior high schools, vocational high schools, Islamic senior high schools, and institutes. The aim of this study is to identify the students' educational backgrounds and to assess their ability to follow Arabic language instruction. This is a qualitative study employing a descriptive method. The data collection techniques used include observation, interviews, and documentation. The results indicate that the students have diverse educational backgrounds, with a total of 81 students residing in Dormitory C. Among them, 35% graduated from general and vocational high schools, and 25% graduated from institutes. Regarding their ability to follow Arabic instruction, 15% of the students from general and vocational high schools demonstrated the ability to understand Arabic instruction, 17% of the students from Islamic senior high schools showed comprehension, and 19% of the students from institutes exhibited a good ability to follow Arabic instruction. Based on these findings, it can be concluded that the students’ ability to follow Arabic language instruction is generally good and is influenced by their educational backgrounds.